Study on absolute eosinophil count correlation with severity of bronchial asthma - Lalrinpuia, Benjamin; P., Naveen (International Journal of Research in Medical Sciences, 2019)
Background: Bronchial asthma is defined as chronic inflammatory disease of the airways that is characterized by increased responsiveness of the tracheobronchial tree to a multiplicity of stimuli. Eosinophil infiltration is a characteristic feature of asthmatic airways. It presents as an obstructive type of ventilator defect usually diagnosed from a reduced FEV1% (Forced Expiratory Volume) or from a reduced peak expiratory flow (PEF) associated with reduced airway caliber during expiration. Allergen inhalation results in a marked increase in activated eosinophils in the airways. Correlation between the degree of bronchial hyperresponsiveness (a cardinal feature of asthma) and peripheral blood eosinophilia has been observed in patients with dual response following allergen challenge. Methods: The study comprises a total number of 50 bronchial asthma patients of both sexes (male and female) between the age groups of 13-65 years. Based on severity, asthma patients were classified into mild, moderate and severe asthmatics, assessed by FEV1% computerized Spirometry Helios model number 701, recorders and medicare system. Peripheral blood sample was collected from each patient for absolute eosinophil count, the count was done on the same day. Results: The mean±SD absolute eosinophil count of 50 patients is 330±88.64 which is slightly above normal (300 cells/mm3). Author found that the mean±SD absolute eosinophil count of 405±83.16 in severe asthma patients is quite high, corresponding with a steep decline in the FEV1% 45.3±12.6. Conclusions: Absolute eosinophil count and FEV1% are important indicators of bronchial asthma severity and can even be used to predict disease progression.